KUAT TEKAN BATA RINGAN DENGAN BAHAN CAMPURAN ABU TERBANG PLTU ASAM-ASAM KALIMANTAN SELATAN - Ninis Hadi Haryanti (Jurnal Fisika FLUX, 2015)
Various researches regarding the utilization of coal fly ash are currently being explored in order to increase its economic value as well as decrease its harm to environment.at the same time. The purpose of this reasearch is to know compressive pressure and weight of light-weight brick by using fired-coal waste from ”Asam-Asam” Coal Fired Steam Power Plant. The test result towards fly ash’s characteristics from ”Asam-Asam” Coal Fired Steam Power which has been done beforehand, is inline with the requirement of SNI 03-2460-1991. However the result of compressive pressure test still meets the requirement of SNI 03-0349-1989.Test has been conducted about compressive pressure and light-weight brick by using mixed materials of fly ash.  The compositions of light-weight brick’s production are cement and fly ash for 50% each, including mixed foam, polymer and hardener, 0.50% for each of them, in order to achieve the highest average result of light-weight brick’s compressive pressure by 39.99 kg/cm2 or 3.92 MPa. Meanwhile its density obtains 0.78 kg/dm3 or 780 kg/m3. ‘D’ light-weight brick’s compositions are cement by 42.86% and fly ash by 28.57% including unslaked lime by 28.57%. Whereas the mixed compositions of foam, polymer and hardener for each 0.50% and 0.38%.The test result above still fulfils the requirement of SNI 03-0349-1989, which is 21 kg/cm2 for the solid concrete brick quality level IV as well as fulfils the theory of light-weight brick according to Tjokrodimuljo (2007), concrete is categorized as light if its weight is less than 1800 kg/m3